Sulfur dioxide flux measurement at Mount Tokachi, Japan, with TROPOspheric Monitoring Instrument - Yamaguchi, Kensuke; Tanaka, Ryo; Morita, Masaaki; Mori, Toshiya; Kazahaya, Ryunosuke (Frontiers in Earth Science, 2023)
Mount Tokachi, in Japan, is an active volcano that experienced three magmatic explosive eruptions in the 20th century (in 1926, 1962, and 1988–1989). Since 2006, geodetic observations have captured ground deformation, suggesting an inflation beneath the main crater. Moreover, since 2020 daily visual observations have detected the increase in plume heights and the occurrence of volcanic glow at the main crater. The high-time-resolution estimation of SO2 flux will help monitor the activity of Mount Tokachi and clarify the associating mechanisms. Furthermore, satellite remote sensing can estimate the vertical column density (VCD) of sulfur dioxide (SO2), enabling the daily determination of SO2 flux without the need to visit the site. Due to the improved spatial resolution, the TROPOspheric Monitoring Instrument (TROPOMI) has advanced satellite-based volcanic gas flux measurements. We have analyzed the available TROPOMI data and conducted ground-based observations to estimate the SO2 flux from Mount Tokachi at 100 – 2000 tons/day. However, a high flux, such as in excess of 2000 tons/day, was observed in the winter season. The flux from the satellite data was similar to that from ground-based observations during the summer. However, a seasonal change in flux from the satellite data was observed in winter, with the flux being larger than that in summer, possibly because the flux increases during winter. Another possible reason is the influence of snow cover on satellite observations due to its high surface reflectance. We reanalyzed some TROPOMI data during the winter, in which the ground snow cover was misidentified as clouds at low altitudes. This procedure suppresses the error caused by the high surface reflectance due to winter snow coverage and improves the quality of the annual SO2 flux from satellite observations. Furthermore, the average annual SO2 flux has been increasing since 2021, on par with the increase in plume height and volcanic glow. Overall, TROPOMI data enabled quantification of the annual SO2 flux, with a sufficient temporal resolution to monitor the volcanic activity at Mount Tokachi.